Contribution of the TIME in BCP-ALL: the basis for novel approaches therapeutics - Poveda-Garavito, Nathaly; Combita, Alba Lucía (Frontiers in Immunology, 2024)
Despite strict regulation of bone marrow (BM) signals to keep their conditions stable. In B-cell precursor acute lymphoblastic leukemia (BCP-ALL), accumulating evidence indicates that leukemic cells can disrupt the physiological hematopoietic niche in the BM, creating a new leukemia-supportive microenvironment, favoring immunological evasion mechanisms and the interaction of these cells with the development and progression of BCP-ALL. With a growing understanding of tumor immune microenvironment (TIME) in the development and progression of BCP-ALL, current strategies focused on "re-editing" TIME to promote antitumor immunity have been developed. In this review, we summarize how TIME cells are disrupted by the presence of leukemic cells, evading immunosurveillance mechanisms, specifically in a BCP-ALL model, the crosstalk between TIME and leukemic cells that conduce to resistance treatment, and the most promising immunotherapy strategies. We choose Frontiers in immunology, especially cancer immunity and immunotherapy because our review takes both topics.